Facile synthesis of CaFe2O4 for visible light driven treatment of polluting palm oil mill effluent: Photokinetic and scavenging study - Charles, Ashwin; Khan, Maksudur R.; Ng, Kim Hoong; Wu, Ta Yeong; Lim, Jun Wei; Wongsakulphasatch, Suwimol; Witoon, Thongthai; Cheng, C. K. (Elsevier B.V., 2019)
In this paper, a facile synthesis method for CaFe2O4 is introduced that produces a catalyst capable of significant photocatalytic degradation of POME under visible light irradiation. The co-precipitation method was used to produce two catalysts at calcination temperatures of 550 °C and 700 °C dubbed CP550 and CP700. CP550 demonstrated the maximum COD removal of 69.0% at 0.75 g/L catalyst loading after 8 h of visible light irradiation which dropped to 61.0% after three consecutive cycles. SEM images indicated that the higher calcination temperature of CP700 led to annealing which reduced the pore volume (0.025 cm3/g) and pore diameter (10.3 nm) while simultaneously creating a smoother and more spherical surface with lower SBET (9.73 m2/g). In comparison, CP550 had a rough hair-like surface with higher SBET (27.28 m2/g) and pore volume (0.077 cm3/g) as evidenced by BET analysis. XRD data indicated the presence of CaFe5O7 in the CP550 composition which was not present in CP700. The presence of Wustite-like FeO structures in CaFe5O7 are likely the cause for lower photoluminescence intensity profile and hence better charge separation of CP550 as these structures in CaFe2O4 have been known to increase resistivity and electron localization. The COD removal of CP550 dropped from 69.0% to just 7.0% upon adding a small quantity of isopropanol into the reaction mixture indicating hydroxyl radicals as the primary reactive oxidative species.